Within- and between-person predictors of disordered eating attitudes among male and female dancers: Findings from the UK Centres for Advanced Training. (November 2016) - Nordin-Bates, Sanna M.; Schwarz, Johanna F.A.; Quested, Eleanor; Cumming, Jennifer; Aujla, Imogen J.; Redding, Emma
Abstract: Objectives: This longitudinal study examined potential predictors of disordered eating attitudes (DEA) for male and female dancers, with a particular focus on whether environmental predictors (perceptions of task- and ego-involving motivational climate) added significantly to the prediction made by intrapersonal predictor variables (demographics/training, self-esteem, perfectionism). Methods and Design: Young dancers (N = 597, 73.4% female, M  = 14.69 years old, SD  = 2.04) from UK Centres for Advanced Training completed questionnaires 1–5 times over a two-year period, depending on how long they were enrolled at their centre. Multilevel modelling was employed to examine both between- and within-person predictors of DEA. Results: For females, lower self-esteem and higher perfectionistic concerns were significant between-person predictors of DEA. Increased levels of perfectionistic strivings and perfectionistic concerns were significant within-person predictors. For males, increased perfectionistic concerns and perceptions of the motivational climate as more task- and ego-involving were significant between-person predictors of DEA. No significant within-person predictors emerged. Conclusions: Findings contribute to the literature on DEA in aesthetic activities and the debate concerning the (mal-)adaptiveness of perfectionistic strivings. They also raise questions about how environmental aspects should best be conceptualized and measured in studies of this type. In particular, however, results demonstrate that the predictors of DEA among males and females may not be the same, and suggest that future interventions may therefore need to be sex-specific. Highlights: Predictors of disordered eating attitudes (DEA) differed for males and females. Only perfectionistic concerns predicted DEA for both sexes. For females self-esteem and perfectionistic strivings were additional predictors. For males task- and ego-involving climate perceptions were additional predictors.